2017
DOI: 10.1088/1361-6463/aa82f6
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of (1−x)KNbO3xNiO two-phase composites

Abstract: We report a detailed study on structural and dielectric properties, Raman scattering, and ac-conductivity of ferroelectric KNbO3 and antiferromagnetic NiO two-phase composites [() KNbO3  +  x NiO]. Two major transitions were observed in the temperature dependent relative dielectric permittivity (T)—the first at C () and the second at C (T1)—respectively associated with the structural transitions from tetragonal to cubic and orthorhombic to tetragonal phases. In addition, a new anomaly across T2  ∼  C has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In order to understand the nature of this hopping mechanism we fitted the experimental data to the equation ρ = ρ o e (To/T) n , where ρ o (pre-exponent factor) and T o is the characteristic temperature coefficient. Both of these constants were extracted from the slope and intercepts of figure 7 [39][40][41]. Usually the exponential value n should be either 0.25 or 0.33 for 3D and 2D systems, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the nature of this hopping mechanism we fitted the experimental data to the equation ρ = ρ o e (To/T) n , where ρ o (pre-exponent factor) and T o is the characteristic temperature coefficient. Both of these constants were extracted from the slope and intercepts of figure 7 [39][40][41]. Usually the exponential value n should be either 0.25 or 0.33 for 3D and 2D systems, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Soni et al recently reported a new anomaly across 593 K in ε r (T) along with the two known transitions at 718 K and 493 K in the FE KNbO 3 and antiferromagnetic NiO composites [21]. These authors also studied the role of NiO in the vibrational spectra of KNbO 3 , and reported the emergence of a two-magnon mode at 1500 cm −1 [21]. Moreover, a very recent study reported structural distortion from orthorhombic to monoclinic phase at room temperature in NNO + NiO twophase composites [14].…”
Section: Introductionmentioning
confidence: 88%
“…These authors also pointed out that the phase transition from the P-phase to the R-phase (T ∼ 643 K) in NNO crystals may be due to dipole relaxation around the offcentre Nb ions, resulting in an order-disorder character of the AFE phase [13]. Soni et al recently reported a new anomaly across 593 K in ε r (T) along with the two known transitions at 718 K and 493 K in the FE KNbO 3 and antiferromagnetic NiO composites [21]. These authors also studied the role of NiO in the vibrational spectra of KNbO 3 , and reported the emergence of a two-magnon mode at 1500 cm −1 [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation